PACKMAN – A portable instrument to investigate space weather. (April 2021) - Mathanlal, Thasshwin; Vakkada Ramachandran, Abhilash; Zorzano, Maria-Paz; Martin-Torres, Javier
Abstract: PACKMAN (PArticle Counter k-index Magnetic ANomaly) is an autonomous, light and robust space weather instrument for operation within the subsurface, surface and atmosphere (as payload in stratospheric balloons) of the Earth. It has been designed using Commercial Off-The-Shelf (COTS) components to reduce the cost of each unit and to allow to have multiple units monitoring simultaneously at different sites and also incorporate an open-access citizen science approach. The hardware-core of each PACKMAN units, weights around 600 g and consumes about 500 mA of current at 12 V. PACKMAN has been deployed at multiple latitudes and altitudes ranging from stratospheric heights (corroborating its TRL8 maturity) to subsurface depths of around 1 km. The data from PACKMAN have been compared with the state-of-the-art ground-based observatories, and satellites and scientific observations have been documented. A 3-D network of PACKMAN units operating continuously around the globe, from the subsurface to the stratosphere, would help to improve the understanding of the space weather phenomena, and its implications on the climate and infrastructures. PACKMAN is also an excellent tool for education and outreach. This article outlines the building instructions of two types of PACKMAN units: PACKMAN-S for ground-based measurements and PACKMAN-B for stratospheric measurements aboard high-altitude balloons.